Sustainability Evaluation of Seaweed Aquabusiness Management in Support of Sustainable Development Goal in Ekas Bay, East Lombok - Naning Dwi Sulystyaningsih; Nur Fadhilah Rahim; Mita Ayu Liliyanti; Evron Asrial; Rusmin Nuryadin; Nuri Muahiddah (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research Based on technological and economic dimensions, the sustainability of seaweed cultivation in Ekas Bay was less sustainable (index value lied between 26 and 50). The distance between seed clumps, drying places, seedling binding locations, and warehouses were the most sensitive attributes from technological dimension. Market status, market scale, and target market were the most sensitive attributes from economic dimension   Abstract Indonesia is one of the major countries in the world that produces seaweed. West Nusa Tenggara has become one of the centers of seaweed producers in Indonesia because it has many bays that are used for seaweed cultivation activities. The problem of seaweed aquabusiness is the low productivity of the production unit managed by seaweed farmers. This study aimed to assess the effectiveness and production level of seaweed cultivation technology and the success of seaweed cultivation by seaweed farmers in Ekas Bay based on technological dimensions (17 attributes) and economics (14 attributes). The Rapsewaqua application is used to analyze the sustainability status of seaweed cultivation. Based on the results of the analysis, the index value was 50.08 for the technology dimension and 39.50 for the economic dimension. The result showed that the sustainability of seaweed in Ekas Bay was in the less sustainable category. Spacing between seed clumps, drying area, seedling binding location, and warehouse were the most sensitive attributes on the technological dimension. Market status, market scale, and target market were the most sensitive attributes in the economic dimension. These sensitive attributes need to be improved to support the sustainability of seaweed in Ekas Bay.